2009
DOI: 10.1002/jbm.a.32418
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro characterization of poly(styrene‐b‐isobutylene‐b‐styrene) copolymer stent coatings for biostability, vascular compatibility and mechanical integrity

Abstract: The TAXUS Express 2 Paclitaxel Eluting Coronary Stent System employs a coating consisting of the thermoplastic elastomer, poly(styrene-b-isobutylene-b-styrene; SIBS), selected for its drug-eluting characteristics, vascular compatibility, mechanical properties, and biostability. This study was conducted to evaluate the impact of different SIBS (17-51 mole % styrene) compositions on mechanical properties, chemical stability, and vascular compatibility. Mechanical property (stress-strain measurements) and stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 21 publications
(25 reference statements)
2
45
0
3
Order By: Relevance
“…properties, it is of special importance that both polymers possess non-immunogeneity and bioand blood compatibility (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). For all these reasons, it is expected that the integration of these two types of polymer segments into one macromolecule may lead to a variety of new application possibilities.…”
Section: Refs 1-29 and References Therein) In Addition To Their Intmentioning
confidence: 99%
“…properties, it is of special importance that both polymers possess non-immunogeneity and bioand blood compatibility (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). For all these reasons, it is expected that the integration of these two types of polymer segments into one macromolecule may lead to a variety of new application possibilities.…”
Section: Refs 1-29 and References Therein) In Addition To Their Intmentioning
confidence: 99%
“…The similarities of hydrophobic characteristics between PTX and monomers of styrene and methyl methacrylate supports facile encapsulation of PTX and provides efficient drug loading in the poly(MMA-ST-AA) nanospheres. Previous studies separately demonstrated that PTX is compatible either with co-polymers consisting of MMA or ST [8,[26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…Styrene blocks give the material a glassy region providing its mechanical rigidity, while the isobutylene blocks provide enhanced chain mobility. Compositions with higher content of styrene have behavior closer to that of a toughened plastic, while the higher isobutylene compositions behave as an elastomeric plastic [1,2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Poly(Styrene-block-Isobutylene-block-Styrene) (SIBS) copolymer is a thermoplastic elastomer that has been proposed to be used in biomedical applications because it is extremely biocompatible and has a very low foreign body reaction [1][2][3]. Mechanical properties of SIBS are similar to polyurethanes and silicone rubbers, which make it ideal for use in stents, drug carriers, MIDI-tubes, heart valves, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation